Changes in light absorption by the chloroplast, related to its structural transformations - J. Zurzycki; H. Gabryś (Acta Societatis Botanicorum Poloniae, 2015)
The changes in light absorption of single chloroplasts and one layer of chloroplasts related to their structural transformations were considered. Theoretical calculations of light absorption (EA) and transmission (ET) as well as for the mean intensity of absorption (IA) for the ellipsoid of revolution were given by the formulas 3,2 and l respectively. It was shown that the true shape of Funaria chloroplasts can be considered as ellipsoid of revolution. From the four conformational states of chloroplasts the most flattened one (corresponding to the low intensity of illumination) absorbs maximal amount of light energy. For the one layer of chloroplasts the changes in light absorption connected with structural transformations were estimated as ca. 4%.